2017
DOI: 10.1371/journal.pone.0169270
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Flavor Characteristics, Fatty Acid Profile, Antioxidant Status and Nrf2-Dependent Antioxidant Enzyme Gene Expression Changes in Young Grass Carp (Ctenopharyngodon idella) Fillets Fed Dietary Valine

Abstract: This study was conducted to examine the effects of dietary valine on the physical and flavor characteristics, fatty acid (FA) profile, antioxidant status and Nrf2-dependent antioxidant enzyme gene expression in the muscle of young grass carp (Ctenopharyngodon idella) fed increasing levels of valine (4.3, 8.0, 10.6, 13.1, 16.9 and 19.1 g/kg) for 8 weeks. Compared with the control group, the group fed valine showed improved physical characteristics of fish fillets (increased relative shear force, hydroxyproline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Valine is one of the essential amino acids in the human body, Luo et al . () showed that with the increase of dietary valine levels, the reduced glutathione (GSH) content and the activities of Cu/Zn superoxide dismutase (SOD1), catalase (CAT) increased, which suggests that dietary valine may have beneficial effects on fish antioxidant defences. The active oxygen scavenging ability is closely related to the antioxidant activity, so the strong antioxidant activity of VYLPR may be due to the valine contained in it.…”
Section: Resultsmentioning
confidence: 99%
“…Valine is one of the essential amino acids in the human body, Luo et al . () showed that with the increase of dietary valine levels, the reduced glutathione (GSH) content and the activities of Cu/Zn superoxide dismutase (SOD1), catalase (CAT) increased, which suggests that dietary valine may have beneficial effects on fish antioxidant defences. The active oxygen scavenging ability is closely related to the antioxidant activity, so the strong antioxidant activity of VYLPR may be due to the valine contained in it.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one of the major contributions of HLM is to enhance fatty acid metabolism. Fatty acids are an important component of cell membrane, and they are also involved in the formation of meat flavor [33,34]. More importantly, unsaturated fatty acids are also involved in immune regulation [35] and neurophysiological effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Further in vitro experiment with primary muscle cells confirmed that leucine activated AMPK/Sirt1 pathway, which favoured continuous replenishment of myofibers. Also, moderate levels of dietary leucine (11.0–13.3 g/kg) and valine (10.6–16.7 g/kg) significantly increased fillet shear force and WHC in grass carp, which were associated with the improved antioxidant capacity through Nrf2 signalling and increased protein deposition via TOR signalling in the muscle 98,102 . Dietary isoleucine supplementation altered the texture profiles in hybrid bagrid catfish ( Pelteobagrus vachelli × Leiocassis longirostris ), characterised by increased resilience, and cohesiveness as well as decreased hardness, gumminess, and chewiness 100 .…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturementioning
confidence: 98%